Surveillance data on micro-organisms in respiratory tract infections at a tertiary care teaching hospital in South India - Shanmugam, Sriram; Thekkinkattil, Mohankumar; Kanayalal, Manish; C, Minu Mohan; Mohnot, Charmie; K, Monisha (International Journal of Research in Medical Sciences, 2017)
Background: Respiratory tract infections are the leading cause of infections and associated hospitalizations in India. Generally, there is little control on the use of antibiotics. Community awareness of the issues involved in antibiotic therapy is poor and this is compounded by over-the-counter availability. The main aim was to compare the resistance developed by respiratory microbes. Methods: A retrospective and prospective study was designed and conducted to compare the pattern of resistance developed by microorganisms affecting the respiratory tract. Results: The sensitivity of K. pneumoniae to cefepime/tazobactum has decreased from 91.9% to 47.6% and S. aureus to Linezolid has decreased from 93.4% to 80% and S. pyogenes to azithromycin from 51.4% to 24.8%. Whereas sensitivity pattern of S. pneumoniae to amoxicillin/clavulanate is increased from 65.6% to 82.3%. The prevalence of Klebsiella pneumoniae was increased 19% to 25.2% whereas the prevalence of S. pneumoniae was decreased from 66.8% to 65.2%. Our study suggests that all microorganisms isolated are susceptible to carbapenems and cefepime/tazobactum in the cephalosporin class. Conclusions: There is major shift in the sensitivity pattern of microorganisms towards antibiotics. Therefore, these results must be kept in mind by the practitioners in the study site, prior to making decisions over a medication regimen empirically for patients and also to maximize the output of medications by rational prescribing and dosing.